Cerebellar Cryptococcoma in an Immunocompetent Adult: A Rare Occurrence Report of a Case and Review of Literature - Kumar, Manish; Bajaj, Ankur; Tewari, Manoj Kumar; Singh, Paramjit; Radotra, Bishan Das (Indian Journal of Neurosurgery, 2020)
This study reports a rare case of cryptococcoma of the brain and review the related literature. An intracranial lesion, in a healthy, middle-aged adult who underwent surgery with a preoperative diagnosis of neoplastic/metastatic lesion, which turned out to be cryptococcoma, is being reported. Histopathological examination revealed that this immunocompetent patient had cryptococcoma of the cerebellum. He responded to antifungal chemotherapy (amphotericin B initially for 2 weeks and later oral fluconazole for 10 weeks) very well. Occurrence of cryptococcomas in immunocompetent patients is rare and responds to antifungal chemotherapy very well. Only six cases (including this) have been reported in literature till now.
Keywords: cryptoccocal infection; cerebellar cryptococcoma; neurotropic; immunocompetent